2022
DOI: 10.1002/btm2.10403
|View full text |Cite
|
Sign up to set email alerts
|

Vascular stiffening in aging females with a hypertension‐induced HIF2A gain‐of‐function mutation

Abstract: Pulmonary arterial hypertension (PAH) is more prevalent in females than males; the causes of this sex difference have not been adequately explored. Gain-of-function (GOF) mutations in hypoxia-inducible factor 2α (HIF2A) lead to PAH and thrombotic consequences in patients and mice. Additionally, multiple emerging studies suggest that elevated systemic arterial stiffening (SAS) occurs in PAH; this could have critical prognostic value. Here, we utilized a HIF2A GOF mouse model to determine how SAS can be used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…We found that some differentially expressed genes including collagens (COL4A), vitronectin, and vWF were significantly altered in the ECM pathway. Studies have shown that collagen deposition thickens the triple-layer structure of pulmonary arteries and induces pulmonary hypertension ( Volkova et al, 2023 ). Inhibition of the HIF-1α signaling pathway reduces UCHL1-induced collagen expression in fibroblasts ( Guo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that some differentially expressed genes including collagens (COL4A), vitronectin, and vWF were significantly altered in the ECM pathway. Studies have shown that collagen deposition thickens the triple-layer structure of pulmonary arteries and induces pulmonary hypertension ( Volkova et al, 2023 ). Inhibition of the HIF-1α signaling pathway reduces UCHL1-induced collagen expression in fibroblasts ( Guo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%